2013
DOI: 10.1007/s10857-013-9266-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an historical perspective on prospective teachers’ beliefs in learning mathematics

Abstract: Many learners hold traditional beliefs about mathematics that can hamper their learning in the discipline. To address this issue, a ''history-based'' intervention program entailing problem-solving and writing activities that instigate cognitive conflict was implemented. Data sources were pretest and posttest scores of a 12-theme questionnaire designed for this study called ''Prospective teachers' beliefs questionnaire about mathematics learning'' and written reflections of prospective teachers. The survey of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…That way we can compare some of our participants' reactions to the reactions of other participants in other projects and experiments. Similar research in groups of participants, 7 / 17 in that case prospective math teachers, not undergraduate students, has been done and shown that facing difficulties and different situations in problems with historical background can change their path of thought and their pedagogical style (Clark, 2012;Furinghetti, 2007;Weldeana & Abraham, 2014). Another approach, closer to ours, is where the researchers suggested to the classroom that they cooperate in solving an open-ended problem, to improve their teamwork skills and come closer to a result (Suastika, 2017).…”
Section: In One Paragraph (Approximately 100 Words)mentioning
confidence: 74%
“…That way we can compare some of our participants' reactions to the reactions of other participants in other projects and experiments. Similar research in groups of participants, 7 / 17 in that case prospective math teachers, not undergraduate students, has been done and shown that facing difficulties and different situations in problems with historical background can change their path of thought and their pedagogical style (Clark, 2012;Furinghetti, 2007;Weldeana & Abraham, 2014). Another approach, closer to ours, is where the researchers suggested to the classroom that they cooperate in solving an open-ended problem, to improve their teamwork skills and come closer to a result (Suastika, 2017).…”
Section: In One Paragraph (Approximately 100 Words)mentioning
confidence: 74%
“…Meskipun bukanlah pendekatan yang sama sekali baru, penerapan model PBL mengalami kemajuan yang pesat di banyak perguruan tinggi dan berbagai disiplin ilmu di negara-negara maju (Tan, 2013). Nigus, Solomon, & Abraham, (2014) mengatakan bahwa As learners are exposed to problems from the history of mathematics that triggers cognitive conflict, they have to deploy problem-solving strategies to resolve the conflict and gain some learning.…”
Section: Pembahasan Model Pembelajaran Problem Based Learning (Pbl)mentioning
confidence: 99%
“…Dan menurut Glazer ( 2001) "Dengan pembelajaran bermakna diharapkan memberikan kemudahan kepada siswa dalam melakukan proses pembelajaran yang utuh". Menurut Nigus et al (2014) If knowing mathematics is a means to able to do the mathematics, the history-based intervention program helped the prospective mathematics teachers' favor knowing math-ematics by diminishing the role of holding a step-by-step procedure and rote memorization in solving mathematics problems. Knowing the mathematics has a correspondence with enabling students to construct their own knowledge by means of ''doing'' mathematics, solving problems, and organizing the subject matter.…”
Section: Pembahasan Model Pembelajaran Problem Based Learning (Pbl)mentioning
confidence: 99%